La muerte del verdadero don Toribio de San Martín Cortés, gobernador de Cuernavaca (1595) - Nadine Béligand (Nuevo mundo - Mundos Nuevos, 2020)
In several Primordial Titles of Cuernavaca, don Toribio de San Martín Cortés appears as the one who synthesizes the collective integrity of the altepetl (Indian seigneury). His profile is the personification of a unity in which government and Christian religion merge. However, the picture is somewhat obscured by chronological distancing. It is thanks to his will, presented in this article, that we can approach the complexity of the character and give an account of the origins of the legend he inspired to successive generations.